MSR under exogenous shock: The case of COVID-19 pandemic - Valeriya Azarova; Mathias Mier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The EU implemented the Market Stability Reserve (MSR) in response to the 2008 financial crisis to deal with short-term impacts of future shocks, such as the COVID-19 pandemic. We link a model that intertemporally optimizes the handling of banked allowances every five years with one that simulates the annual working of the EU ETS including the MSR with its potential cancelling. Neglecting the pandemic, 2.16 billion allowances are cancelled. Accounting for the pandemic, 0.28 billion additional allowances are cancelled if the European economy fully recovers by 2021, which even overcompensates the 2020 drop in CO2 emissions. Additional cancelling increases when the pandemics lasts longer, meaning that the MSR even outperforms its initial purpose.
Keywords: C61; H23; Q41; Q51; Q54; Q58; 330; COVID-19 pandemic; EU ETS; Market Stability Reserve; Decarbonization